Hail Satan? [videorecording (DVD)] - Lane, Penny, 1978- (Magnolia Home Entertainment, 2019)
"When media-savvy members of the Satanic Temple organize a series of public actions designed to advocate for religious freedom and challenge corrupt authority, they prove that with little more than a clever idea, a mischievous sense of humor, and a few rebellious friends, can speak truth to power in some truly profound ways. A timely look at a group of often misunderstood outsiders whose unwavering commitment to social and political justice has empowered thousands of people around the world."--Container.